AMYAND'S HERNIA -A RARE CASE OF RIGHT -SIDED IN INGUINAL HERNIA - Shumenkovski, Velimir; Arnaudov, Dimitar; Trenchikj, Bojan; Antovikj, Svetozar; Ognjenovikj, Ljubomir; Kostovski, Ognen; Volchevski, Goce; Hadzi Manchev, Dragan; Trajkovski, Gjorfji (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Amyand’s hernia is the presence of the appendix in the inguinal hernia sac. The prevalence of this type of inguinal hernia is about 1%. Majority of cases of Amyand’s hernia are incidentally diagnosed during surgical treatment of inguinal hernia. Amyand’s hernia typically presents on the right side since right-sided inguinal hernia is more common and the appendix is located in the lower right quadrant of the abdomen.    We present a case of a 23-year-old patient hospitalized at the University Clinic for Digestive Surgery in Skopje for elective surgical treatment of right-sided inguinal hernia.   Keywords : Amyand’s hernia, inguinal hernia, appendix.